Prevalence and clinical presentation of Post-COVID syndrome in patients recovered from acute COVID infections in North Kerala - Sarin SM; Surag MK; Rijit Kannan; Mukundan PK; Ranjit Kumar KC; Aishwarya Sureshbabu K (Asian Journal of Medical Sciences, 2023)
Background: Post-acute COVID symptoms have become a major health concern and one of the most important causes of morbidity throughout the world. Hence, it is important to document the pattern of presentation in post-COVID syndrome patients in India, which has been one of the countries with the largest acute COVID-19 infections. Aims and Objectives: This study was done to estimate the prevalence of post-acute COVID syndrome in patients recovered from acute COVID infection and to determine the factors influencing with its incidence. Materials and Methods: Community-based observational study in which patients who have recovered from acute COVID infection 3–6 months before the study period were selected using multistage sampling. Data were collected through house visits using a pre-validated questionnaire containing details of acute COVID-19 infection, treatment taken, vaccination status before the infection, symptoms in the period between 4 and 12 weeks, and symptoms after 12 weeks of acute COVID infection. Results: Out of the 265 patients studied, 14.34% had ongoing symptomatic COVID-19 in the first 3 months of acute illness and 9.81% had post-COVID symptoms even after 3 months. 17.74% of the patients had a history of pre-existing comorbid illnesses and 31.32% had received two doses of vaccination before acquiring COVID-19 infection. 92.83% were treated in home quarantine, 4.91% needed hospitalization without oxygen supplementation, and 2.26% required oxygen or ventilatory support. The most common post-COVID symptoms reported were tiredness, easy fatiguability, breathlessness, and body ache. Female gender, presence of comorbidities, and mode of treatment had a significant role in predicting the incidence of post-COVID symptoms. Conclusion: The study clearly showed that the severity of acute COVID infection has a significant correlation with the incidence of both ongoing symptomatic COVID and post-COVID syndrome. Other factors that increased the incidence included female gender and pre-existing comorbidities.